Documents of the Society of Doctors at the Kazan University as a historical source (second half of the 1920s) - R.G. Ivanova; A.A. Salnikova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper describes the complex of documents that appeared as a result of the activities of the Society of Doctors at the Kazan University in the second half of the 1920s. These documents are stored in the Museum of History of Kazan State Medical University, thereby contributing greatly to the overall archive of the Society of Doctors at the Kazan University during the pre-revolutionary period, and in the National Archive of the Republic of Tatarstan. The sources under the study are the unique documents, which have been for the first time used for the purposes of research, concerning the specific activity of the society during the establishment of the Soviet healthcare system. The society was founded in 1868, i.e., it can be considered as one of the oldest medical corporate associations in Russia. Its activities in the 1920s influenced greatly the general state of medical and social spheres in Kazan, Tatar Republic, and Russia, as well as determined the development of other medical communities. It has been proved that the principle of inextricable link between theory and practice, which later became the basis of Soviet medicine, laid at the core of the society's activities. The paper proves the integrity and continuity of the studied documents, identifies information capabilities of various groups of sources as its components. Based on the obtained data, the conclusion has been made about the sufficient representativeness of the studied sources for exploration of the social history of societies at the Kazan University. The introduction of this documentary collection to scientific use has allowed not only to restore the important aspects of organizational, administrative, and scientific activities of the Society of Doctors at the Kazan University in the second half of the 1920s, but also to explore the less known aspects of the Kazan University and Soviet healthcare history.